2008
DOI: 10.1111/j.1399-3062.2008.00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Acanthamoeba infection in a patient with chronic graft‐versus‐host disease occurring during treatment with voriconazole

Abstract: We report a case of disseminated infection with Acanthamoeba in a patient with graft-versus-host disease after hematopoietic stem cell transplant (HSCT) for acute lymphocytic leukemia. The infection involved the brain, skin, and lungs and occurred despite treatment with voriconazole for mold prophylaxis, and did not respond to treatment with multiple other agents reported to have activity against Acanthamoeba. To our knowledge, infection with Acanthamoeba has been reported in 4 other patients after HSCT or bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Recently, cases of amoebic meningoencephalitis have been found in healthy persons [7] and in haematopoietic stem cell transplanted patients [2,5,9,13]. It seems that recipients of HSCT may be at increased risk for life-threatening amoebic infections as well as the difficulty in making an ante mortem diagnosis of GAE.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, cases of amoebic meningoencephalitis have been found in healthy persons [7] and in haematopoietic stem cell transplanted patients [2,5,9,13]. It seems that recipients of HSCT may be at increased risk for life-threatening amoebic infections as well as the difficulty in making an ante mortem diagnosis of GAE.…”
Section: Discussionmentioning
confidence: 98%
“…In immunocompromised hosts, the most common manifestation of disease is subacute meningoencephalitis [33]. Skin lesions have rarely been reported, as in a patient with acute lymphocytic leukemia who developed extensive GVHD and became septic, with papular, ulcerative lesions on his face and extremities; histology of these sites confirmed presence of Acanthamoeba, despite being on prophylactic therapy with voriconazole.…”
Section: Cutaneous Acanthamoeba Infectionmentioning
confidence: 91%
“…The patient was started on liposomal amphotericin B (5 mg/kg) daily in combination with trimethoprim-sulfamethoxazole (5 mg/kg of the trimethoprim component) every 8 h, but patient expired 5 weeks after diagnosis. Risk factors for development of this infection include: solid organ transplantation, connective tissue disease, diabetes, cirrhosis, renal failure, malignancy, and tuberculosis [33].…”
Section: Cutaneous Acanthamoeba Infectionmentioning
confidence: 99%
“…Reports also exist of proven breakthrough infections in patients receiving other agents for MAP, including voriconazole and echinocandins [42,43]. A retrospective review of HSCT patients receiving voriconazole prophylaxis showed that although IA was rare, zygomycosis occurred in 6% of patients and invasive candidiasis in 8% [44].…”
Section: Breakthrough Invasive Fungal Infectionmentioning
confidence: 96%